Restorative effect of insulin-like growth factor-I gene therapy in the hypothalamus of senile rats with dopaminergic dysfunction - Hereñú, Claudia Beatriz (2007)
Insulin-like growth factor-I (IGF-I) is emerging as a powerful neuroprotective molecule that is strongly induced in the central nervous system after different insults. We constructed a recombinant adenoviral vector (RAd-IGFI) harboring the gene for rat IGF-I and used it to implement IGF-I gene therapy in the hypothalamus of senile female rats, which display hypothalamic dopaminergic (DA) neurodegeneration and as a consequence, chronic hyperprolactinemia. Restorative IGF-I gene therapy was implemented in young (5 months) and senile (28 months) female rats, which received a single intrahypothalamic injection of 3 × 109 plaque-forming units of RAd-βgal (a control adenoviral vector expressing β-galactosidase) or RAd-IGFI and were killed 17 days post-injection. In the young animals, neither vector modified serum prolactin levels, but in the RAd-IGFI-injected senile rats a nearly full reversion of their hyperprolactinemic status was recorded. Morphometric analysis revealed a significant increase in the total number of tyrosine hydroxylase-positive cells in the hypothalamus of experimental as compared with control senile animals (5874±486 and 3390±498, respectively). Our results indicate that IGF-I gene therapy in senile female rats is highly effective for restoring their hypothalamic DA dysfunction and thus reversing their chronic hyperprolactinemia.